2012
DOI: 10.1016/s0924-9338(12)75701-2
|View full text |Cite
|
Sign up to set email alerts
|

The willingness to participate in health research studies of individuals with Turkish migration backgrounds: barriers and resources

Abstract: The willingness to participate in health research studies can be increased through particular efforts, which should be tailored to the recruitment of the underrepresented target population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 27 publications
2
37
0
7
Order By: Relevance
“…There are no other studies that we are aware of with refugees’ perspectives on research engagement with which to compare our results. Of note, our research findings about refugees are in line with previous findings about the perspectives of ethnic minorities more generally [14,15], however, this study also elicited unique variables not previously identified in the literature.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There are no other studies that we are aware of with refugees’ perspectives on research engagement with which to compare our results. Of note, our research findings about refugees are in line with previous findings about the perspectives of ethnic minorities more generally [14,15], however, this study also elicited unique variables not previously identified in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…A 2012 German study [14] with Turkish migrants, a 2005 Canadian study [15] with migrant women, and a 2003 American study [3] of African American, Latino and Chinese Americans all used qualitative methods to elicit participant perspectives on research. These studies, by adding participants’ voices, have resulted in greater understanding of ethnic minority participants’ willingness to engage in health research and suggestions have been made for culturally appropriate research designs for minority participant involvement [2,4,5,8,10,14,16]. With respect to the opinions of refugees in particular, one longitudinal cohort study of refugee youth in Australia [17] asked refugee participants about their experiences having engaged with the research study for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is possible that individuals who were already mentally burdened were more likely to participate in the survey, presumably because they had less fear of discussing the topic of mental strain or perhaps because they were hoping for a supportive conversation. In this context and as a possible explanation for the very low response rate of the study, a qualitative focus group investigation prior to the survey also indicated that the participants had strong prejudices and mistrust in research studies [62]. A further aspect might be the fear of lacking data protection and stigmatization within the Turkish community in the case of participation.…”
Section: Discussionmentioning
confidence: 99%
“…To identify barriers to participation in the target group and to improve the survey participation rate, several focus groups with individuals with Turkish migration backgrounds were conducted [28]. After conducting a comprehensive research of available survey material, selected interview instruments (i.e., the computerized Composite International Diagnostic Interview, Diagnostic Expert System Interview, shortened: CIDI DIA-X Version 2.8 and questionnaires were subsequently translated into Turkish [29].…”
Section: Methodsmentioning
confidence: 99%